2016
DOI: 10.5858/arpa.2014-0367-rs
|View full text |Cite
|
Sign up to set email alerts
|

Ewing Sarcoma/Primitive Neuroectodermal Tumor of the Kidney: A Rare and Lethal Entity

Abstract: Ewing sarcoma/primitive neuroectodermal tumor represents a spectrum of undifferentiated tumors with similar biology that together represent the second most common sarcoma in the pediatric-young adult age range. Very rarely, this tumor presents as a primary neoplasm of the kidney. The clinical presentation of this tumor is not specific, and other renal tumors may present with a similar histologic appearance. Establishing the correct diagnosis is critical because renal Ewing sarcoma/primitive neuroectodermal tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…The CT scan of our patient showed a large adrenal tumor with a heterogeneous contrast enhancement. Celli and Cai reported this same aspect regarding primitive kidney Ewing sarcoma as the imagery reveals an ill-defined renal mass, with heterogeneous contrast enhancement and intermixed necrosis areas and hemorrhage [6]. The magnetic resonance imagery (MRI) scan allows a better appreciation of the involvement of soft tissues in Ewing's tumor [7].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The CT scan of our patient showed a large adrenal tumor with a heterogeneous contrast enhancement. Celli and Cai reported this same aspect regarding primitive kidney Ewing sarcoma as the imagery reveals an ill-defined renal mass, with heterogeneous contrast enhancement and intermixed necrosis areas and hemorrhage [6]. The magnetic resonance imagery (MRI) scan allows a better appreciation of the involvement of soft tissues in Ewing's tumor [7].…”
Section: Discussionmentioning
confidence: 79%
“…On gross examination, the median size of the tumor is about 13 cm and is characterized by confluent areas of necrosis and hemorrhage [6]. Histologically, neuroectodermal tumors are composed of uniform small round cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC studies showed more than 90% positivity for CD99, but CD99 is not specific and cannot be used as an absolute biomarker for its diagnosis [7], [8].…”
Section: Discussionmentioning
confidence: 99%
“…Wilms' tumor is positive for WT1 and usually negative for chromogranin and synaptophysin [14]. Primitive neuroectodermal tumor of the kidney is immunoreactive for CD99 and negative for WT1 [15]. Metanephric adenoma is positive for WT1 and negative for EMA [16].…”
Section: Discussionmentioning
confidence: 99%